Can youtube be trusted as a source of quality and reliable information on COVID-19 vaccination in Italy? - Gentile, Leandro; Bertuccio, Paola; Ancona, Angela; Cucchi, Andrea; Dallagiacoma, Giulia; Godoy, Martino Alberto; Signorelli, Carlo; Odone, Anna (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Social media platforms are common sources of information, even more so during the COVID-19 pandemic. YouTube is the second most popular social media platform both in Italy and globally. Following criticisms regarding quality control during the pandemic, banners that would direct viewers to official health information sources were incorporated into Youtube videos related to COVID-19. The aim of this study is to assess the reliability and information quality of YouTube videos related to COVID-19 vaccination in Italy. Methods: On March 2022, six different search queries were used to retrieve COVID-19 vaccination-related videos, resulting in the identification of 329 videos, and their characteristics were described. Two validated instruments, namely HoNCode and DISCERN, were used to assess the reliability and quality of the videos’ content. Results: Of the total number of videos, 72.0% were from non-medical or generalist channels. The most represented category was internet media (32.5%) while the less frequent was educational medical channel (7.0%). Videos from medical channels had higher reliability (p=0.002) and quality (p<0.001) than not medical channels, despite receiving fewer visualizations (p=0.004), likes (p=0.018) and comments (p<0.001). Media and news agencies sources consistently delivered lower quality content. Conclusions: These findings suggest that public health professionals and institutions should consider investing in social media representation to fill the gap with non-medical sources in terms of popularity, to provide reliable and interesting videos, and ultimately deliver health education to the general public.